Material synthesis and design optimization of biomaterials for biomedical implant applications - Nilesh Tipan; Ajay Pandey; Pushyamitra Mishra (BioImpacts)
Introduction: In the modern era, the use of biomaterials in orthopaedics has revolutionised the healthcare sector. Traditionally, some non-biodegradable materials such as titanium and stainless steel are used as biomaterials. However, issues such as toxicity, poor tissue adhesion, and stress-shielding effect can occur with non-biodegradable materials for bone fracture fixation. Several biodegradable materials have been developed to resolve these issues but have not yet been appropriately industrialized for implant applications. These substances can be classified into metals, ceramics, and polymers, which can be blended to create composites that enhance biocompatibility and biomechanical characteristics. Methods: This study began by contrasting the biocompatibility and mechanical compatibility among various alloys: biodegradable low entropy (BLE) alloys, biodegradable medium entropy (BME) alloys, biodegradable high entropy (BHE) alloys, and non-biodegradable medium entropy (NBME) alloys. Additionally, the design morphology of bio-implants like plates, screws, and others was inspected. Moreover, a meta-analysis was conducted to optimize the design of biomaterials, ensuring appropriate biocompatibility and degradation rate. A subsequent statistical analysis was executed to determine the optimal material concentration for bio-implant alloy creation. Results: Initially, in this paper, the advantages of biodegradable materials over conventional non-biodegradable materials are discussed and bibliometric analysis is done to show recent research contributions in the field of biomedical implant application. Then compared biocompatibility and mechanical compatibility among BLE alloys, BME alloys, BHE alloys, NBME alloys. Furthermore, investigated the design morphology of bio-implants such as plates and screws. Also presented a meta-analysis for design optimization of biomaterials to meet suitable biocompatibility and biodegradation rates and presented a statistical analysis among them, which helps to select the appropriate material concentration for bio-implant alloy formation. Conclusion: It was observed that in biodegradable materials, tensile strength is in the pattern of NBME > BHE > BME > BLE, and the degradation rate is in the pattern of BME > NBME > BHE > BLE. This study suggests that biodegradable materials (BLE and BME) are a much better choice than non-biodegradable materials in orthopaedic applications. It was also observed that a Biodegradable locking compression plate (BLCP) can provide the necessary strength and performance. Further, the systematic meta-analysis presented herein furnishes crucial data to researchers, guiding them in enhancing the efficiency of diverse biomaterials and optimizing their designs.